The effect of a 24-week physiotherapy and occupational therapy program in systemic sclerosis: a monocentric controlled study with follow-up - Špiritović, Maja; Šmucrová, Hana; Heřmánková, Barbora; Oreská, Sabína; Štorkánová, Hana; Rathouská, Adéla; Česák, Petr; Komarc, Martin; Růžičková, Olga; Bunc, Václav; Pavelka, Karel; Vencovský, Jiří; et al. (Clinical and Experimental Rheumatology, 2022)
OBJECTIVES: The structural and functional changes of the hands and face in systemic sclerosis (SSc) can be severely disabling. We aimed to assess the effect of a 24-week supervised physiotherapy and occupational therapy program (POTp) combined with home exercise on the function of hands/mouth of SSc patients, compared to a daily home exercise program in typical outpatient care. METHODS: Fifty-nine patients with SSc were consecutively and non-selectively enrolled in an intervention (IG, n=27) or control (CG, n=32) group. Only the IG underwent the POTp twice a week for 1.5 hours. At baseline, 12, 24, and 48 weeks, all patients were assessed by a blinded physiotherapist for the hands/mouth function (delta finger-to-palm, handgrip strength, Hand and Mobility in Scleroderma, interincisal/interlabial distance), and self-evaluated their hand (Cochin Hand Function Scale) and mouth function (Mouth Handicap in Systemic Sclerosis scale), disability (Health Assessment Questionnaire [HAQ], SSc HAQ), and quality of life (Short Form-36). RESULTS: At week 24, compared to the significant deterioration in the CG, we found a significant improvement in the IG in the objectively assessed hands/mouth function and in the subjectively evaluated hand function and disability. The improvement was clinically meaningful (by >20%) in a substantial proportion of patients. Although the improvement in most outcomes was still present at week 48, the maximum effect was not sustained. CONCLUSIONS: This 24-week POTp not only attenuated the progressive deterioration, but also significantly improved the function of the hands/mouth, which was clinically meaningful in a substantial proportion of patients with SSc.
Keywords: následné studie; techniky fyzikální terapie; Humans; lidé; síla ruky; posuzování pracovní neschopnosti; systémová sklerodermie; Disability Evaluation; Follow-Up Studies; Physical Therapy Modalities; Quality of Life; kvalita života; Occupational Therapy; Scleroderma, Systemic; ergoterapie; Hand Strength